Persuasive Communication of DKBP3A as a Form of Early Marriage Prevention Power to Minimize Domestic Violence and Perpetrator’s Mental Disorders - Wahyuningsih, Sri; Kurniasari, Netty Dyah; Manafe, Yeremia Djefri; Andriyanto, Riski Bayu; Putri Efendi, Devian Ayu (Personifikasi: Jurnal Ilmu Psikologi, 2024)
The purpose of this study is to know, analyze, and explore, persuasive communication of stakeholders of DKBP3A as a form of early marriage prevention power to minimize domestic violence and mental disorders of perpetrators. The research method uses descriptive qualitative, constructivistic paradigm, with a case study approach. Informant technique using purposive sampling, The subject in this study is DPKP3A Bangkalan. The object of his research is persuasive communication of DKBP3A stakeholders as a form of early marriage prevention power to minimize domestic violence and mental disorders of perpetrators. Data collection techniques through observation of in-depth interviews, documentation, audio-visual materials. Data analysis techniques by reducing data, playing data by making categories and discussions, and drawing conclusions. Validity techniques through triangulation and member check. Research Location in Madura. Persuasive communication from DKBP3A in suppressing early marriage to minimize domestic violence and mental disorders is  by socializing the prevention of early marriage, socializing the ideal age for marriage, pre-wedding socialization for prospective brides and grooms going directly to the village through GENRE (Generation Planning), socializing through pamphlets, socializing through banners, and can also use persuasive communication through social media that reaches teenagers, because of his tendency to play social media. As for other findings, apart from socialization, there are obstacles in running the program, namely there is no budget support from the government in 2023. The solution is that DKBP3A continues to run the program by reaching out to the lower classes of society together with cadres who have been previously trained so that the DKBP3A program continues to run.